Identification of Misconception of Animal Tissue Material on Students of Senior High School of 2 Meulaboh Districts Aceh Barat - fathur hadyan; Khairil Khairil; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Research has been conducted to identify problems of misconception that occur in understanding animal tissue material on students of Senior High School of 2 Meulaboh Districts Aceh Barat. Data collection was done by written test in the form of diagnostic test and interview. Diagnostic tests are made in the form of multiple choice with open reasoning accompanied by CRI Score. Data were analyzed by calculating the percentage of each answer and CRI score chosen by the students. The results showed that the average level of (T) totally guess answer as much as 19.46%, TTK (Do not Know the Concept) as much as 27.31%, TK (Know the Concept) as much as 31.74%, and M (Misconception) as 21, 49%. Telah dilakukan penelitian untuk mengindentifikasi permasalahan miskonsepsi yang terjadi dalam memahami materi jaringan hewan pada Siswa SMA Negeri 2 Meulaboh Kabupaten Aceh Barat. Pengumpulan data dilakukan dengan tes tertulis berupa tes diagnostik dan wawancara. Tes diagnostik dibuat dalam bentuk pilihan ganda dengan alasan (reasoning) terbuka yang disertai dengan skor CRI. Data dianalisis dengan cara menghitung persentase dari setiap jawaban dan skor CRI yang dipilih oleh siswa. Hasil penelitian menunjukkan bahwa rata-rata tingkat (T) Tebakan sebanyak 19,46 %, TTK (Tidak Tahu Konsep) sebanyak 27,31%, TK (Tahu Konsep) sebanyak 31,74%, dan M (Miskonsepsi) sebanyak 21,49%.